UNVEILING THE ORIGINS AND METHODS OF FORMATION OF MEDICAL TERMINOLOGY - Mamatova Nilufar Abdukhoshimovna,; Abdulhairova Firuza Invarovna,; Gofurova Gulmira Mannopovna,; Makhmudova Gulchekhra Dilshadbekovna, (The Bioscan, 2024)
This article focuses on the evolution of English medical terminology. While in the past, medical terms were primarily created morphologically by combining Latin and Greek word elements, today, the syntactic method is more prevalent. This involves forming complex terms that are later abbreviated or turned into acronyms. Besides the usual methods, there are also less common ways of forming terms. Understanding the meanings of these uncommon medical terms requires studying their etymology and the reasons behind their creation. Medical terminology is particularly intriguing as it illustrates the interplay between extralinguistic and linguistic factors.